Cu(ii)-based DNA labeling identifies the structural link between transcriptional activation and termination in a metalloregulator. Issue 6 (21st January 2022) - Casto, Joshua; Mandato, Alysia; Hofmann, Lukas; Yakobov, Idan; Ghosh, Shreya; Ruthstein, Sharon; Saxena, Sunil
Abstract : Herein, we exploit site-directed Cu(ii )-labeling to measure the DNA conformations in each step of the transcription cycle of the Copper Efflux Regulator (CueR), in order to establish how transcription is activated and terminated. Abstract : Understanding the structural and mechanistic details of protein-DNA interactions that lead to cellular defence against toxic metal ions in pathogenic bacteria can lead to new ways of combating their virulence. Herein, we examine the Copper Efflux Regulator (CueR) protein, a transcription factor which interacts with DNA to generate proteins that ameliorate excess free Cu(i ). We exploit site directed Cu(ii ) labeling to measure the conformational changes in DNA as a function of protein and Cu(i ) concentration. Unexpectedly, the EPR data indicate that the protein can bend the DNA at high protein concentrations even in the Cu(i )-free state. On the other hand, the bent state of the DNA is accessed at a low protein concentration in the presence of Cu(i ). Such bending enables the coordination of the DNA with RNA polymerase. Taken together, the results lead to a structural understanding of how transcription is activated in response to Cu(i ) stress and how Cu(i )-free CueR can replace Cu(i )-bound CueR in the protein-DNA complex to terminate transcription. This work also highlights the utility of EPR to measure structural data under conditions that are difficult to access in order to shed light on protein function.